Comprehensive Investigation of the Role of Individuals, the Immediate Social Environment, and Neighborhoods in Trajectories of Adolescent Antisocial Behavior in Chicago, Illinois, 1994-2002 - Sullivan, Christopher ([Verlag nicht ermittelbar], 2012)
The overall goal of this study was to acquire a greater understanding of the development of adolescent antisocial behavior using data from the Project on Human Development in Chicago Neighborhoods (PHDCN). Longitudinal cohort data from PHDCN were analyzed to assess patterns of substance use and delinquency across three waves for three age cohorts and 78 neighborhoods. This analysis of existing PHDCN data used multiple cohort and multilevel latent growth models as well as several ancillary approaches to answer questions pertinent to the development of adolescent antisocial behavior.